Reflection on the “One Health” concept, understanding its role in preventive health: integrative review (Research, Society and Development, 2023)
Objective: to address the existing interrelationships between the triad: man, environment and agent from the perspective of One Health, understanding how the application of this thought results in actions aimed at prevention and awareness. Analyzing its role in the face of environmental changes that cause pandemic events, natural disasters and climate change. Method: search was carried out on 07/08/2022 in the BVS and SCIELO databases according to PRISMA guidelines, broadly and methodologically addressing the proposed content. Result: thirteen studies were included, contemplating professionals from different areas to add a multisystemic view to the material, realizing that a common point between the authors is that there is a gap between theory and practice, requiring the development of interdisciplinary strategies that leave the theoretical framework. Conclusion: One Health must act within a framework that encompasses the community, professionals and governments in order to develop actions with a collective focus in a collaborative and participatory way in making social decisions, using environmental education and health promotion as the main tools